Analisis Persepsi Siswa SMP terhadap Pembelajaran Matematika ditinjau dari Perbedaan Gender dan Disposisi Berpikir Kreatif Matematis - Anggoro, Bambang Sri (Al-Jabar: Jurnal Pendidikan Matematika, 2016)
This research is a qualitative research with the qualitative descriptive method. The technique of research subject taking in this research use purposive sampling technique. The subjects of this study amounted to 9 students. Data collection techniques used were questionnaire perception and disposition of students' mathematical creative thinking, observation, interview and documentation of mathematics learning. Data analysis techniques, namely data reduction, data presentation, and conclusions. The validity of data in this study using the content validity, construct validity and reliability and triangulation techniques. According to the results of the study and discussion, the conclusion of this study is Based on the gender and disposition of mathematical creative thinking, the perception of mathematics learning that is produced, that is for high DBKM and positive perception is only found in male students, for high DBKM and medium perception, Male and female students, for medium DBKM and medium perception, female students tend to be more than male students, for medium DBKM and negative perceptions of male students tend to be more than female students, for low DBKM and perception is being Only in boys, and for low DBKM and negative perceptions are only found in female students. The disposition of high mathematical creative thinking and positive perception is very influential on learning mathematics because students who have high DBKM and positive perception will be better in learning mathematics than students who have DBKM and perceptions other than high DBKM and positive perceptions of mathematics learning.